Efficiency Institution Baitul Maal Tamwill in The Westdistrict Bandung - Annisa Nur Hakim; A Jajang W Mahri; Aas Nurasyiah (Universitas Pendidikan Indonesia, 2020)
Abstract. Baitul Maal Wat Tamwil has experienced development in recent years. However, based on BMT performance data in West Bandung regency is less optimal. It is known that there are one efficient BMTs in West Bandung Regency and three BMTs that are inefficient. The cause of BMT's less optimal performance is inefficiency in operational activities. This study aims to determine the level of efficiency of BMT in the West Bandung 2011-2017 period and find out the causes of inefficiency. This study uses secondary data from four BMTs in West Bandung District, which are sampled. The research method used is the descriptive method with Data Envelopment Analysis (DEA) analysis technique to measure the level of efficiency of a company. Input variables used are operating expenses, total assets, and TPF. Furthermore, the output variables used are SHU, income, and financing. Based on the results of research conducted, the conditions of the BMT in the West Bandung Regency have not been perfectly efficient. Three BMTs have experienced inefficiencies, including BMT Dana Ukhuwah, BMT Mustama, and BMT Rabbani. Keywords. Efficiency, Baitul Maal Wat Tamwil, Data Envelopment Analysis